Effect of Operant Conditioning in an Athetoid for Improving Dexterity - Vidya Hosakote (Journal of All India Institute of Speech and Hearing, 1970)
Operant conditioning procedures have been applied to improve verbal ex- pression of non-verbal children, aphasics,  (Kerr,  et al 1965,  Dembros 1966), elective  mutism  cases,  stutterers  and  schizophrenics to  improve  work  skills (Girerdean and  Spradlin,  1964,  Bensberg,  1965,  etc.)